Evaluation of a Weight-Based Mycophenolate Mofetil Dosing Protocol for Kidney Transplant Maintenance Immunosuppression - Mahoney, Melanie Tess; Kincaide, Elisabeth Lapp; Nelson, Joelle; Klein, Kelsey Anne; Hall, Reed Charles; Bhayana, Suverta (Journal of Clinical Nephrology, 2023)
To evaluate the safety and efficacy of weight-based mycophenolate mofetil (MMF) dosing in adult kidney transplant recipients (KTR), this single-center retrospective study of adult KTR compared biopsy-proven acute rejection (BPAR), infections, hospitalizations, granulocyte colony-stimulating factor (G-CSF) use, and MMF dose changes within one year of transplant pre-and post-implementation of a weight-based MMF dosing protocol. Adult patients who received a kidney transplant at University Health Transplant Institute were reviewed for inclusion. Patients in the weight-based MMF group received 1000 mg twice daily by the first clinic visit if ≥ 80 kg, 750 mg twice daily if 50-79 kg, and 500 mg twice daily if < 50 kg. Patients in the fixed-dose MMF group received MMF 1000 mg twice daily. A total of 170 KTR (50.0% ≥ 80 kg, 44.1% 50-79 kg, 5.9% < 50 kg) were included. Baseline characteristics were similar between groups. The majority of patients were middle-aged Hispanic males and received lymphocyte-depleting induction therapy. Incidences of BPAR, infection, and hospitalization were similar between both groups at one-year post-transplant. Weight-based MMF dosing is safe and effective in adult KTR.